Lafadz Musytarak Dinamisasi Dalam Rumah Makna - Ahmad Haromaini (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2019)
As a medium of human communication, the role of language is very important for human life. Language helps him express what is in his mind that is applied in the language system, even though it is intrinsically arbitrary